The role of teacher’s supervision during the development of school recess - Artavia-Granados, Jenny María (2014)
School recess is a space that tries to reach multiple purposes, among them: rest and play time for students; but, is also a good opportunity for teachers to observe student´s behavior outside the classroom. School  recess supervision by teachers and administrative staff turns out to be a fundamental task to achieve prevention or resolution of conflicts that may take place during this school period. This article outlines the development of monitoring the school playground or recess, carried out by teachers from a school at Dirección Regional de Occidente (Western Regional Bureau of Education). From a qualitative research called “Games and social interaction in recesses and its relationship with violent behaviors: the case of 6th grade students.” Its objectives, attempted to analyze the role of the teaching and administrative staff during school recesses. Facing the phenomenon of violence, the school has a social engagement to provide a peaceful solution to the conflicts that may arise. However, the findings show that teachers did not assume fully the supervision of recess, that the majority of teachers considered did not consider supervision as one of their duties, and that there are significant differences between  the conceptualization of the school recess supervision by the principal’s office and the teachers.